Using Audience Commitment to Increase Behavior Changes in Sustainable Landscaping - Laura Sanagorski; Paul Monaghan (EDIS)
Participants in an Extension rain barrel workshop who said they would inspect their irrigation systems might begin to see themselves as people who use water wisely. Their perception of themselves as conservationists is strengthened with each new action. That makes them more likely to agree to an action that leads to an even bigger water savings. Research has shown that commitments can increase the percentage of people who will adopt a new behavior and give up an old one. This 4-page fact sheet was written by Laura A. Sanagorski and Paul Monaghan, and published by the UF Department of Agricultural Education and Communication, September 2013. http://edis.ifas.ufl.edu/wc154